World Trade Organization : a guide to the framework for international trade - Lal Das, Bhagirath (Third World Network PenangMY, 1999)
Provides a detailed and intelligible guide to the intricacies of the WTO agreements. Explains the provisions as they now stand in non-technical language while taking care not to detract from their legal accuracy.